POS EKONOMI DIGITAL SEBAGAI REGUALASI PENINGKATAN SERAPAN TENAGA KERJA UMKM DI DI DESA PRAGAAN DAYA KEC. PRAGAAN KAB. SUMENEP - Abrori (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2022)
Micro, Small and Medium Enterprises (MSMEs) have a significant contribution in improving the Indonesian economy. Increasing the contribution of MSMEs to national growth must continue to be pursued. MSMEs play an important role in the expansion of job opportunities and employment, as well as the growth of gross domestic product (GDP). Based on data from the ministry of cooperatives and MSMEs, MSMEs have been able to absorb around 97% of the workforce in Indonesia, and the contribution of MSMEs to GDP reaches 61.07% in 2020. As a supporter of the economy, micro, small and medium enterprises should be empowered to improve the quality of growth economy and is expected to be a solution to economic inequality. Conditions in Pragaan Daya village, which is part of Sumenep Regency, MSMEs engaged in various products have always recorded quite high growth in the last few years. However, in 2020-2021 the number of MSMEs in Pragaan Daya village has decreased due to the impact of the Covid-19 pandemic and the implementation of Large-Scale Social Restrictions (PSBB) which have an impact on the limited activities of MSMEs.